The Role of Requirements In Agile System Realization. (28th October 2015) - Ann Rosser, Larri
Abstract: Requirements play a fundamental role in the realization of systems, regardless of the methodology used. Current understanding of requirements usage is strongly influenced by traditional program lifecycle paradigms. This paper highlights the fundamental contribution of requirements to system realization, reviews typical requirements usage, quality attributes and assumptions, and identifies areas where a different perspective on requirements usage can enhance agility.